(untitled) (Gaceta Técnica, 2022)
The Consultative Council of the City of Barquisimeto in Venezuela, seeking to promote citizen interest in the activities that address issues related to the sustainable development of the capital of Lara, held in September 2021 within the framework of the VI annual conference, the event THINK THE CITY POST COVID. Motivated by the emergency generated by COVID-19, is about the great responsibilities that must be assumed on a global scale in the face of the accelerated changes that are taking place. Various exhibitors participated from various cities around the world, with various themes addressing issues with the aim of improving urban life, through the articulation of what is new and what already exists in COVID or Post COVID. Greater use of infrastructure, buildings and industrial sectors in disuse and promote them, strengthening neighborhoods, diversifying their uses, without having to move